About Terms of Rational Management of Using of Common Oil and Gas Resources of Ukraine: The Problem of Garmonization of Goals and Interests of Key Groups of Impact - Варцаба, В. І.; Кісь, С. Я.; Петренко, В. П.; Ревтюк, Є. А. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2015)
Based on the analysis of evaluations of NSC "Naftogaz Ukraine" stated the fact of unsatisfactory performance of the company declared in its charter assignments, indicating an incomplete and poor performance of state-owned enterprise of their social obligations to the state and the people of Ukraine. Pointing to the current inability of the authorities adequately to intervene and regulate the processes that occur in the industry, the article identified possible ways and task of restoring the effectiveness and efficiency of the oil and gas complex of Ukraine by putting into practice the internal and external management of the Company’s social responsibility concept, and on the basis of Analysis of spatial patterns of positioning Pareto optimal point on the surface of the utilitarian features of an effective market interaction of the three key players in the oil and gas sector of the domestic market needs to offer adequate socially responsible management of the sector management technologies and recommendations for its effective use.